El internet y su influencia en los procesos de aprendizaje de la Unidad Educativa Enrique Ponce Luque del tercer año de bachillerato del paralelo a del periodo 2016 - De Loor Bravo, Joffre Javier (2016)
The world is changing. Internet is changing the habits of life of modern society. The technology has permeated the lives of the people and tools such as the Internet and social networks are now part of the everyday life of the people, transforming significantly the way we communicate with each other. The new generations have not been outside these transformations. In the same way that some have grown up in his time, for example, influenced by the rise and growth of computing or video games, the young people of today, the owners of the future, are doing the same with the Internet: They were born with the network, are growing up with the network and are living with the network. In the field of education is evidence this phenomenon. The students manage to perfection the social networks, are registered in more than one social network, they are allowed to upload photos, videos and comment on many subjects of their interest, thus creating their own digital identity; but they do not take advantage of the benefits that this tool gives them with regard to their learning